An Errors Analysis in Using Tenses of Students Writing Text at Senior High School - Syaprizal Syaprizal; Ramadona Ramadona (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objective of this investigation was to investigate students errors in writing recount text made by the eleventh grade students of social program Senior High School Number 1 and Senior High School Number 2 Muara Beliti in academic year 2016/2017. The method applied in this investigation was descriptive method. The subject of the investigation was all the eleventh grade students of social program Senior High School Number 1 and Senior High School Number 2 Muara Beliti. The number of the sample was 30 that consist of five students each class and each school. To get the data, the writer used essay test. The test given was an intruction to compose a paragraph in 150 words. Based on the finding of data analysis from the test. The majority errors done by the Eleventh Grade of Social Program Students of Senior High School Number 1Muara Beliti was Verb (55.36 percent) total errors was 62. Punctuation and spelling (4.46 percent) total errors was 5. Preposition (5,35 percent) total errors 6. Pronoun (34.83 percent) total errors was39.The majority errors donethe Eleventh of social program Grade Students of Senior High School Number 2 Muara Beliti wasVerb (61.67 percent) total errors was 37. Punctuation and spelling (1.66 percent) total errors was 1. Preposition (1.66 percent) total errors was1. Pronoun (35.01 percent) total errors was21. In conclusion, The students did such errors because the students translated directly from Indonesian language into English. Therefore, they forgot to use the correct pattern of a sentence that consist subject, verb, and object. Keywords: Writing, Errors, Tenses Analysis, Recount Text.